Energy efficiency of construction processes as an instrument for economic potential growth of real estate development company - Rosynskyi, A.; Onofriichuk, I. (Ways to Improve Construction Efficiency, 2020)
Analyzing the current state of energy efficiency of the construction industry in Ukraine and identifying the main directions of state support for the process of its improvement, the authors of the article investigate the energy efficiency of construction production. It is noted that judging from the experience of implementation of energy efficient projects, the energy efficiency indicator of a building is not a constant that is set during the design, but has a variable nature over its life cycle. Considering this issue to be poorly researched and at the same time important for the full development of construction, energy efficiency at every stage of its life cycle is considered as a complex system. Measures are proposed to improve the energy efficiency of construction processes and to consider its impact on the economic potential of a real estate company. It is determined that in practice, the issue of reducing specific energy costs (for water, heating, lighting, etc.) at the PPP, POB and PVP stage is often not even addressed by contractors, translating all actual energy costs to the customer whose role the developer plays in this context. A number of measures for reducing energy efficiency are proposed, namely: reducing energy costs to support the microclimate of sanitary facilities, use of alternative energy sources, reducing the consumption of water resources for the needs of construction production, optimizing the schedule of construction works, energy efficient selection of machines, mechanisms works. The importance of energy efficiency in construction processes for a real estate company is confirmed by the efficiency of its work. The state of fixed assets of construction enterprises of Ukraine and their importance for the level of energy efficiency of construction processes are analyzed separately. The article proposes measures to improve the energy efficiency of the construction production process, as well as its impact on the economic potential of the development company. The state of fixed assets of construction enterprises and its importance for the level of energy efficiency of construction production are analyzed separately.